The Profit Analysis of Kemplang Fish Business in Pemulutan, Ogan Ilir, South Sumatera - Sari, Lia Perwita; Mayasari, Santi (University of Jember, 2023)
Fish kemplang is a processed of fish product made from fish and sago flour. In South Sumatra, fish kemplang is used as a special food for snacks. The majority of kemplang processing businesses are still medium and small scale. Ogan Ilir is a district that has a lot of kemplang processing centers. Marisah's kemplang business is one of the kemplang businesses in Pelabuhan Dalam Village, Pemulutan District, Ogan Ilir Regency. This business empowers the community surrounding, especially housewives. The purpose of this study was to determine the analysis of Kemplang profit from Mrs. Marisah's business in Pelabuhan Dalam Village, Pemulutan Induk District, Ogan Ilir Regency. The Location was determined by purposively. The research respondents were determined by case study method. Data was analyzed by descriptive qualitative and descriptive quantitative. The results of this study were shown by the production costs of Ibu Marisah's Kemplang business, it consisted of fixed cost and variable costs. Fixed cost was Rp.15,250/day, while variable cost was Rp. 2,856,250/day, so the total costs incurred was IDR 2,871,500/day. The revenue obtained from this business was IDR 3,240,000/day and the income was IDR 368,500/day. The Calculation of the R/C ratio was 1.13, it indicated that Mrs. Marisah's kemplang business was feasible.